CLINICAL AND ETIOLOGICAL PROFILE OF MALIGNANT ASCITES WITH SPECIAL REFERENCE TO SAAG CRITERIA AND BIOLOGICAL MARKERS - JENA, AMALENDU; PARIDA, SURYAKANTA; SAMAL, SATYAJIT; SAMANTARAY, SATYA PRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim and objective of the study are to the analysis of the various patterns of malignant ascites (MA) in our setup. Methods: This prospective observational study was conducted from November 2008 to August 2010 in the Postgraduate Department of General Medicine, S.C.B. Medical College, Cuttack. Diagnosed patients with ascites due to malignancy (intra-abdominal or extra-abdominal) were enrolled into the study. A thorough history and clinical examination were recorded. Patients underwent abdominal paracentesis in the first 24 h after the admission. Ascitic fluid was obtained from the left lower abdominal quadrant and samples were sent for biochemical, cytological, and microbiological analysis. Results: Among 62 patients, male predominance was 71% and mean age of presentation was 55±20.5 years. Histopathological study revealed malignant cells in 32 cases in their ascitic fluid and was classified as MA or peritoneal carcinomatosis. In 30 patients, the ascitic fluid was negative for malignant cells and was classified as malignant-related ascites (MRA). The most common cancers causing MA were gastric (62.5%) followed by ovarian (25%). The most frequently associated cancers in MRA were hepatobiliary (53.3%) and ovarian (13.3%) cancers. Biomarkers were positive in total 32 cases. All 32 patients with carcinomatous peritonitis demonstrated a low (<1.1 mg/dL) serum ascites-albumin gradient (SAAG) and all 30 patients with MRA had high SAAG (>1.1 mg/dL). Conclusion: The incidence of MA was 51.61% and MRA was 48.39%, and highest incidence was seen in the elderly males. SAAG was diagnostic in differentiating MA from MRA with an accuracy of 100%.